Universal Language - Almutairi, Norah (East Carolina University, 2016)
Universal language is the language that everyone can use to communicate with others without considering their spoken language. Nonverbal communication is an effective, universal method of successful communication. The hypothesis is there is a universal language that everyone can communicate with through the use of nonverbal communication methods. This thesis includes an introduction, which shows the original definitions of verbal and nonverbal communication, and six main chapters. The first three chapters focus on neural linguistic programming (NLP), body language, and the unconscious mind. This is an intense literature review about what has been researched and studied in the field of nonverbal communication and provides evidence supporting the hypothesis. The last three chapters focus on an interview with Dr. Rai D'Honore, a survey, and the conclusion.
Keywords: Nonverbal communication